Juridical Analysis of Forestry Criminal Law Enforcement by Corporations in Environmental Fiqh Framework - Mangkunegara, RM. Armaya (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The application of the precautionary principle in enforcing forestry law in Indonesia is a very important principle for protecting forests and the environment. This precautionary principle emphasizes efforts to prevent environmental damage and avoid irreversible risks. This research aims to analyze the application of the Precautionary Principle in Forestry Criminal Law Enforcement carried out by Corporations from the perspective of juridical jurisprudence and the environment. This research employs normative legal methods using various approaches, including the environmental fiqh approach, statutory approach, conceptual approach, case approach, and comparative approach. Implementation of the Precautionary Principle in the context of forestry crime cases involving corporations can be realized through the application of the principle of strict responsibility. The government has issued Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction (P3H) as a step to improve Law Number 41 of 1999 concerning Forestry. Judges who handle cases against companies that violate Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction (P3H) must consider the existing situation and conditions, taking into account the level of damage that has occurred and the impact of forest damage caused by the corporation. From an environmental fiqh perspective, the precautionary principle is in line with the concept of preserving nature (hifz al-bi'ah) which is part of maqasid al-shariah (goals of sharia). This research suggests increasing the capacity of law enforcement through training and outreach regarding the precautionary principle, as well as closer integration between positive law and environmental fiqh values ​​within the framework of forestry criminal law.